Mass of Abrikosov vortex in high-temperature superconductor YBa $$_2$$ 2 Cu $$_3$$ 3 O $$_{7-δ }$$ 7 - δ - Roman Tesař (Nature Portfolio, 2021)
Abstract For more than four decades, mass of Abrikosov vortices defied experimental observations. We demonstrate a method of its detection in high-temperature superconductors. Similarly to electrons, fluxons circulate in the direction given by the magnetic field, causing circular dichroism. We report the magneto-transmittance of a nearly optimally doped thin YBa $$_2$$ 2 Cu $$_3$$ 3 O $$_{7-δ }$$ 7 - δ film, measured using circularly polarized submillimeter waves. The circular dichroism emerges in the superconducting state and increases with dropping temperature. Our results confirm the dominant role of quasiparticle states in the vortex core and yield the diagonal fluxon mass of $$2.2 × 10^8$$ 2.2 × 10 8 electron masses per centimeter at 45 K and zero-frequency limit, and even larger off-diagonal mass of $$4.9 × 10^8 m_e$$ 4.9 × 10 8 m e /cm.